The Effect of Dry Cupping Therapy on Reducing Uric Acid Levels at Griya Terapi Amuskin Besuki Tulungagung: Pengaruh Terapi Bekam Kering Terhadap Penurunan Kadar Asam Urat di Griya Terapi Amuskin Besuki Tulungagung - Saputri, Esy Linda; Sukanto, Sukanto; Surtini, Surtini (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Gout is one of very painful arthritis disease which caused by the solid crystals within the joint. Uric acid can be treated by one of non-pharmacological therapies namely Dry Cupping therapy. Dry Cupping is kind of cupping therapy that does not followed by excretion of blood. Dry Cupping is suitable for people who cannot withstand of needle injection, incision and blood phobia. The research aimed to know the effect of Dry Cupping therapy toward the reduction of uric acid level at Griya Terapi Amuskin Besuki Tulungagung.The researcher used pre-experimental research with one-group Pretest and Post-test design. The population sample contained all of the uric acid patients in Griya Terapi Amuskin Besuki Tulungagung. The researcher conducted accidental sampling technique which contained of 25 people. Dry Cupping therapy was used as the Independent variable and the reduction of uric acid levels was used as the dependent variable of this study. The data was analyzed by wilcoxon signed rank test. The result showed that there was an effect of Dry Cupping therapy toward the reduction of uric acid level at Griya Terapi Amuskin Besuki Tulunganggung. It was showed by P value = 0,000 and α = 0,05 which mean (P < 0,05). It concludes that Dry Cupping therapy helps the reduction of uric acid levels. It was caused by the cumulation of moist pathogens within the meridian. Therefore, the pathogens are cleaned by detoxification process and wind exertion. Thus, cupping therapy is needed for the alternative way of reducing the uric acid levels.